2011
DOI: 10.1002/mren.201000049
|View full text |Cite
|
Sign up to set email alerts
|

In‐Line Monitoring of Particle Size during Emulsion Polymerization under Different Operational Conditions using NIR Spectroscopy

Abstract: In the present work, the sensitivity of NIR spectroscopy toward the evolution of particle size was studied during emulsion homopolymerization of styrene (Sty) and emulsion copolymerization of vinyl acetate–butyl acrylate conducted in a semibatch stirred tank and a tubular pulsed sieve plate reactor, respectively. All NIR spectra were collected online with a transflectance probe immersed into the reaction medium. The spectral range used for the NIR monitoring was from 9 500 to 13 000 cm−1, where the absorbance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…35 A recent study from our group on the monitoring of acetic anhydride hydrolysis 30 needed no NIR spectra pretreatments; on the other hand, more complexes systems, such as miniemulsion and emulsion polymerization, required preprocessing. [4][5][6][7][8]12,14,16,17 ■ CONCLUSIONS NIR spectroscopy is an efficient method to monitor the chemical and physical properties of processes. Calibration models can be constructed to monitor properties with fast dynamics and be extended to monitor other systems with fast kinetics.…”
Section: Industrial and Engineeringmentioning
confidence: 99%
See 3 more Smart Citations
“…35 A recent study from our group on the monitoring of acetic anhydride hydrolysis 30 needed no NIR spectra pretreatments; on the other hand, more complexes systems, such as miniemulsion and emulsion polymerization, required preprocessing. [4][5][6][7][8]12,14,16,17 ■ CONCLUSIONS NIR spectroscopy is an efficient method to monitor the chemical and physical properties of processes. Calibration models can be constructed to monitor properties with fast dynamics and be extended to monitor other systems with fast kinetics.…”
Section: Industrial and Engineeringmentioning
confidence: 99%
“…Thus, NIR chemometric models require a multivariate calibration. The statistical technique most applied to spectra data treatment is partial least squares (PLS). , ,, In order to construct a calibration model, a training set with known concentration (or conversion, diameter, or any property of interest) is necessary. This property should be analyzed using well-established analytical methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have also employed near-infrared spectroscopy (NIR) to predict the particle size, for instance, in the emulsion polymerization of methyl methacrylate, copolymerization of styrene/butyl acrylate , or copolymerization of vinyl acetate/butyl acrylate, butyl acrylate/styrene miniemulsion copolymerization, dispersion polymerization, styrene suspension polymerization, and vinyl chloride suspension polymerization, where the particle size varies between tens of nanometers to a few millimeters between these systems. These studies demonstrated that the NIR spectrum is affected by the particle size distribution.…”
Section: Introductionmentioning
confidence: 99%